Geographical developmental specificities of aggregative resource potential of farm economies of Ukraine throughout 2011–2017 - Руденко, Валерій Петрович; Руденко, Степан; Заячук, Мирослав Дмитрович (My University, 2022)
The study focuses on the analysis of geographical developmental specificities of the potential of Ukrainian farm economies over seven years period (2011–2017). We assessed the average annual cost estimate of interconnected labor, material, and land resources that form the aggregative potential for the development of farms in Ukraine. Labor, material, and land resources were assessed through the cost estimate (money value). The cost of a commodity is defined as social labor embodied in the same. The cost is measured by money. Hence, money estimates are labor estimates. Labor resources and the units of labor produced by an average annual farm employe were counted through the labor’s funds analog, that is, through the annual totality of employees’ wages divided by the normative coefficient of efficiency of capital investments. Agricultural machinery, i.e., tractors, combine harvesters, corn harvesters, forage harvesters, seeders, windrowers, etc., available on farms in 2011–2017, were the basis for the assessment of material resources (capital assets). Bringing non-recurring (capital) costs to a per-year basis (to be comparable with other resources) was carried out by way of counting percentages of the current production assets following their established efficiency standard (0.15). Estimation of land resources based on natural productivity of Ukrainian lands, that is, on crop capacity gained on condition that crop rotation, was observed. The range of works on the mechanical treatment of arable land was applied, and no fertilizers were added. The Ukrainian farms’ aggregative resource potential was presented as a sum of the potentials of labor, material, and land resources. According to our calculations, the aggregative potential throughout 2011–2017 was 52 019 million hryvnias, or 2 771 million euros.
Економічної географії та екологічного менеджменту
Keywords: farm economies of Ukraine; aggregative resource potential; money value